Doctrinal Dialogue: (Importance, Types and Controls) - Altashlan, Shorouq Mohammed (Journal of Islamic Sciences, 2021)
The Islamic world has been afflicted with many tribulations, from exaggeration and incomplete interpretation of texts and their interpretation, so it has been easy for people to accuse Muslims of heresy, unbelief, ignorance and polytheism in controversial issues that are not the subject of these descriptions, but rather are not a place for ignorance and error, so it is enough for blasphemy and innovation? and the incurable disease that has spread in our time, and led to The emergence of many contradictions is the absence of the Sunnah of dialogue, which is the most important task. The rules of dialogue and difference and its controls are the determinant between the interlocutors from falling into extremism, insult or non-acceptance of the truth. In this research, a statement and definition of dialogue and its importance, types, style and controls, which we conclude through: 1) Dialogue is a divine method, one of the most highly-constructed concepts as stated in the Holy Qur’an. 2) Dialogue is one of the most beneficial means by which one arrives at the truth 3) Commitment to the controls of dialogue is the shortest way to reach the desired goal of dialogue and achieve the desired results. 4) The Qur’an’s dialogue with the polytheists, the infidels and the hypocrites, each according to his condition and belief. The polytheist would have a dialogue of guidance and the hypocrites, a dialogue of severity, violence and threats, and the infidels had a dialogue of defiance and intimidation.